Evolution of Intermetallic Compounds between Sn-0.3Ag-0.7Cu Low-silver Lead-free Solder and Cu Substrate during Thermal Aging - Mookam, Niwat; Kanlayasiri, Kannachai (My University, 2012)
The growth, transformation, and lattice structure of intermetallic compounds formed between Sn-0.3Ag-0.7Cu lead-free solder and copper substrate were investigated. Dip soldering was used to initiate the reaction between the solder and substrate. An η-Cu 6Sn 5 intermetallic phase possessing a hexagonal lattice structure was found at the as-soldered interface. Thermal aging at a number of conditions resulted in the formation of a Cu 3Sn intermetallic phase between the Cu 6Sn 5 layer and the copper substrate. e{open}-Cu 3Sn with an orthorhombic lattice structure was found together with hexagonal Cu 3Sn. Subsequently, the activation energies of the intermetallic phases were calculated and compared to results obtained from the literature. The comparison showed that good agreement existed between the findings from this study and literature data within a similar temperature range. © 2012 The Chinese Society for Metals.
Keywords: Activation energy; Intermetallics; Microstructures; Soldering